(3GdNUNUI hCKQgG Ydi GdJfejI HGdOhd GdfGejIs - (3YHOg eMeO aGVd(B, (3GdQHjYjs ((3GdbGgQI(B:s (3ecJHI eOHhdj(B,s, 2004)
(3OhQ GdbWGY GdYGe aj GdJfejI hCSGSg GdGbJUGOj, OhQ GdbWGY GdNGU aj GdJfejI, OhQ GdbWGYjf GdYGe hGdNGU aj GdJfejI HGdOhd GdfGejI, GdNUNUI hCSGSgG GdGbJUGOj , JLQHI LeghQjI Tjdj aj GdNUNUI, JLQjI LeghQjI eGdjRjG aj GdNUNUI, JLQHI LeghQjI JQcjG aj GdNUNUI, JLQHI LeghQjI eUQ aj GdNUNUI, OhQ GdbWGYjf GdYGe hGdNGU aj GdJfejI HGdLeghQjI GdjefjI, JLQHI GdLeghQGdjefjI aj GdGUdGM GdGbJUGOj, JLQHI GdLeghQjI GdjefjI aj GdNUNUI, Jbhje GdJLQHI GdjefjI aj Xd JLGQH GdOhd GdCNQi, OQhS eSJaGOI(B.s
(3GdeQGLY U(B.503s
Keywords: (3EdZGA GdJCejes; (3GdHdOGf GdfGejIs; (3GdJfejI GdEbJUGOjIs